More answers

Lvl 2

-13

Q: What is the middle term of the product of (x - 4)(x - 3)?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

(4x+1)(4x-3)

8

If that's - 4x, the answer is (2x + 3)(2x - 5) If that's + 4x, the answer is (2x - 3)(2x + 5)

It is: -3(4x-0.50) = -12x+1.50 or as 1.50-12x

Suppose the least number is x. Then the greatest is 2x and the middle is x+3. So x + (x+3) + 2x = 75 ie 4x+3 = 75 or 4x = 72 or x = 18 So the three numbers are 18, 21 and 36.

Related questions

4x + 3

8x + 8 = 4x 4x + 8 = 0 4x = -8 x = -2

4x - 1 = 11 4x = 12 x = 3

-1 Here is why: let x be the number, 4x+7=3 4x=3-7=-4 so 4x=-1 and x is -1

3+4x=15 4x=15-3 4x=12 x=12/4 x=3 The check is: If x=3 then, 3+ (4 X 3)=15 3+12=15

(4x^4 - x³ + 17x² + 11x + 4) ÷ (4x + 3) = x³ - x² + 5x - 1 remainder 7. Do the division via long division, looking at the highest power of x in the dividend: _________________x³ ___- x²_ + 5x - 1 ________----------------------------------- 4x + 3 | 4x^4 - x³ + 17x² + 11x + 4 _________4x^4 + 3x³ _____________________ ← x³(4x + 3); x³ in the quotient _________-------------- _______________- 4x³ + 17x² ______________ ← subtract and bring down next term (+ 17x²) _______________ -4x³ __ -3x² ______________ ← -x²(4x + 3); - x² in the quotient _______________--------------- ______________________ 20x² + 11x ________ ← subtract and bring down the next term (+ 11x) ______________________ 20x² + 15x ________ ← 5x(4x + 3); + 5x in the quotient ______________________ -------------- ______________________________ -4x + 4 ____ ← subtract and bring down the next term (+ 4) ______________________________ -4x - 3 _____ ← -1(4x + 3); -1 in the quotient ______________________________ -------- ___________________________________ 7 ______ ← subtract; no more terms to bring down, this is remainder.

It is possible to factorise 4x²-9 further.Factorising is to express a number or expression as a product of factors.The technique of factorising two terms: a² - b² = (a + b) (a - b)If we apply ( 4x²-9 ) to the previous technique: 4x² - 9 = (2x + 3) (2x - 3)

-9 < 4x + 3 < 11 Subtract 3 from each expression: -12 < 4x < 8 Divide each term by 4: -3 < x < 2

(4x2 - 13x - 12)/(4x+ 3) = (4x + 3)(x - 4)/(4x + 3) = (4x + 3)(x - 4)/(4x + 3) = x - 4 :)

4x + 3 doesn't factor. It is in its simplest form.

F.O.I.L= First, Outside, Inside, Last.Example: (2x+3)(4x+5)First: 2x X 4x = 8x2Outside: 2 X 5 = 10Inside: 3 X 4x = 12xLast: 3 X 5 = 15________________Final result: 8x2+12x+25

Let the unknown number be X: -4x-10 = 2 -4x = 2+10 -4x = 12 x = -3 Remember that a minus multiplied by a minus is equal to a plus: -4*-3 = 12